2021
DOI: 10.1007/s10098-021-02135-7
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of caffeine and E. coli inactivation using silver oxide nanoparticles obtained by a facile green co-reduction method

Abstract: In this study, silver oxide nanoparticles (Ag 2 O-NPs) were synthesized from silver nitrate using green amaranth leaf extract as reducing agent. The degradation of caffeine and inactivation of Escherichia coli by Ag 2 O-NPs was studied under compact uorescent lamp illumination irradiation. Apart from that, the antibacterial and antioxidant activities of Ag 2 O-NPs were also examined. Synthesized Ag 2 O-NPs were shaped like monodispersed husk, and cubic structured with surface area and average particle size was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The authors reported that concentrations of 50 and 100 mg mL À1 of nanocrystals of Ag 2 O do not affect cell viability over 24 h. 30 However, Muthukumar et al suggest that concentrations below 30 mg mL À1 Ag 2 ONPs may be used for biomedical applications since higher concentrations would be dangerous for non-cancerous cells. 25 In summary, cytotoxic studies showed that the combination of the concentrations 0.5/1.0 mg mL À1 of Ag 2 ONPs/antibiotics respectively, do not affect the cell viability of HDF (Fig. 8).…”
Section: Cytotoxic Effectmentioning
confidence: 85%
See 3 more Smart Citations
“…The authors reported that concentrations of 50 and 100 mg mL À1 of nanocrystals of Ag 2 O do not affect cell viability over 24 h. 30 However, Muthukumar et al suggest that concentrations below 30 mg mL À1 Ag 2 ONPs may be used for biomedical applications since higher concentrations would be dangerous for non-cancerous cells. 25 In summary, cytotoxic studies showed that the combination of the concentrations 0.5/1.0 mg mL À1 of Ag 2 ONPs/antibiotics respectively, do not affect the cell viability of HDF (Fig. 8).…”
Section: Cytotoxic Effectmentioning
confidence: 85%
“…24 It is important to emphasize that the MIC exhibited by the present Ag 2 ONPs against reference strains and resistant and MDR clinical isolates, were in the lower range of MIC values previously reported for Ag 2 ONPs synthesized by physical and biological methods. 24,25,29…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional waste water treatment processes have failed to successfully degrade caffeine and hence it is imperative to design new technologies for efficient treatment of caffeine-contaminated wastewater. In this respect, there have been a few reports on the successful degradation of caffeine using photocatalysts like Ag 2 O, Mg-doped ZnO-Al 2 O 3 , and NiO/TiO 2 -F. [38][39][40] However, the reports are very scanty in number and much more research work is necessary to augment the applicability of photocatalysis in the treatment of caffeine-contaminated wastewater. Hence, in this work caffeine was chosen as a model pollutant to establish a technology for efficient degradation of caffeine and also to study the photocatalytic activity of the developed Nb-doped V 2 O 5 samples.…”
Section: Photocatalytic Activitymentioning
confidence: 99%